The foundation stage teacher in action: teaching 3, 4 and 5 year olds - Edgington, Margaret (London ; Thousand Oaks : SAGE Publications, Paul Chapman, 2004)
`The book takes a deeper insight into the role of the practitioner and provides invaluable information Nursery Education `I think the book would be good value for money for anyone working within a foundation stage team' - Foundation Stage File `The Foundation Stage Teacher in Action is one of the definitive texts on the foundation stage, in which Margaret Edgington deals with the realities of practice based on theory and early years principles. It is immensely practical and easy to read, and while it deserves to be read from cover to cover, this New Edition is particularly accessible for those who want to dip in or who need to refer to a specific chapter' - Early Education `If you are new to the Foundation Stage, have been working in the Early Years for a few years, or for longer than you care to remember, if you have responsibility for employing staff for the Foundation Stage within your setting or if you work in a different key stage but have co-ordinator responsibility for the Foundation Stage, you should buy this book!' - National Campaign for Nursery Education Newsletter 'This is classic in the world of nursery education and this Third Edition, with its new title reflecting the changes in that world, is as exciting and challenging as earlier versions. Margaret Edgington's campaigning zeal is undiminished as she asserts the prime need for specialist teachers to work with young children in the Foundation Stage and backs this claim with authoritative research references. This is a strong, passionate authoritative text and I shall keep it close to hand for my own work' - Marian Whitehead, Nursery World `This is the third generation of books dealing with the pedagogy of the early years from Margaret Edgington, the first two being her editions of The Nursery Teacher in Action, originally published under the name Margaret Lally. The changes that have come about in early years education - notably the introduction of the Foundation Stage with its accompanying curriculum guidance and assessment requirements - meant that many early years books have needed updating. This Third Edition is more than an update; it represents some very hard thinking about what practitioners now need to know to be effective, and presents this by revisiting the original book's themes' - Escalate `Paul Chapman Publishing and Margaret Edgington have pulled off a real gem of a book, with updated sections (thank you for the Forest school stuff, for example!) and fresh insights. The hard work has really paid off - thanks so much' - Nick Swarbrick, Oxford Brookes University `This Third Edition brings a broader perspective to the early years world. Margaret's years of experience as a practitioner and consultant in the field are evident and she manages to blend good practice, policy and theoretical aspects, bringing an astute yet sensitive approach to the early years practitioners' varied experiences and qualifications. The book reaches not only those who are starting on their careers as early years practitioners, but also those who have been there a long time and witnessed many, often bewildering changes, where their beliefs and practice have been challenged. The new edition should be essential reading not only for those working in the field, whatever stage in their careers, but also for anyone who seeks to understand small children and support them in the best way possible' - Angela D Nurse, Head of Department of Childhood Studies, Canterbury Christ Church University This is a fully revised and updated edition of the author's best selling book The Nursery Teacher in Action, Second Edition. This book now includ
College Audience
BIED
Keywords: Education, Preschool; Education, Primary; Preschool teachers -- Training of -- England; Teacher-student relationships -- England; Preschool teachers -- Training of; Teacher-student relationships